Analisis Penggunaan Mobile Banking Syariah dalam Meningkatkan Akses Keuangan Masyarakat Pekanbaru - Febri Delmi Yetti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This paper aims to analyze how the use of Islamic mobile banking can improve financial access for the people of Pekanbaru by understanding the features, adoption rates, and factors that influence its use. A descriptive qualitative approach is used to analyze the experiences, adoption, and obstacles of the people of Pekanbaru in using Islamic mobile banking, with primary data obtained through in-depth interviews and participant observation and secondary data from bank documents and related literature. Data collection was conducted through triangulation through interviews, observations, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña (2014) through the stages of condensation, presentation, and verification of conclusions. The results of the study provide a comprehensive overview of the contribution of Islamic mobile banking to improving public financial access, the level of user comfort, and the obstacles faced. The results of this paper show that the use of Islamic mobile banking in Pekanbaru has been proven to facilitate public access to financial services by enabling fast savings transactions, transfers, bill payments, credit purchases, and zakat via mobile phones. This service increases efficiency, reduces queues at the counter, and simplifies customer account management. The growth in active users and transaction volumes indicates that Islamic mobile banking is well-received and plays an important role in expanding financial access and optimizing banking technology.